Pengaruh Hedonic Shopping Motivation dan Electronic Word of Mouth terhadap Impulse Buying Konsumen - Dimas Ilyafa; Ratih Tresnati; Moch. Malik Akbar (UNISBA Press, 2022)
ABSTRACK. This study aims to determine the implementation of Hedonic Shopping Motivation, E-WOM (Electronic Word of Mouth), and Impulse Buying on Eiger Products, and to find out how much influence Hedonic Shopping Motivation and E-WOM (Electronic Word of Mouth) partially have. and simultaneously on Impulse Buying on Eiger Products in Subang City. The problems found in this study, namely Hedonic Shopping Motivation and E-WOM (Electronic Word of Mouth) have not been able to encourage Impulse Buying on Eiger products because a number of consumers do not shop spontaneously, a number of consumers do not shop without thinking, and a number of consumers do not shop because emotional considerations. This study uses a survey method using non-probability sampling technique for sampling. And the type of non-probability sampling technique chosen is incidental sampling technique. This study uses a descriptive verification type of research with a quantitative approach. The population in this study are consumers of Eiger products in Subang City. This study took a sample of 100 respondents. Multiple linear regression analysis is a data analysis method used in this study which aims to determine the direction of the relationship between the independent variables, namely Hedonic Shopping Motivation (X1) and E-WOM (Electronic Word of Mouth) (X2) with the dependent variable being Impulse Buying (Y). The results of this test state that the Hedonic Shopping Motivation and E-WOM (Electronic Word of Mouth) variables each partially have a significant effect on Impulse Buying, and simultaneously the Hedonic Shopping Motivation and E-WOM (Electronic Word of Mouth) variables have a significant effect on Impulse Buying on Eiger products. Abstrak. Penelitian ini bertujuan untuk mengetahui implementasi Hedonic Shopping Motivation, E-WOM..(Electronic Word of Mouth), dan Impulse Buying pada Produk Eiger, serta untuk mengetahui seberapa besar pengaruh Hedonic Shopping Motivation dan E-WOM (Electronic Word of Mouth) secara parsial dan simultan terhadap Impulse Buying pada Produk Eiger di Kota Subang. Masalah yang ditemukan dalam penelitian ini yaitu Hedonic Shopping Motivation dan E-WOM (Electronic Word of Mouth) belum mampu mendorong Impulse Buying pada produk Eiger dikarenakan sejumlah konsumen tidak berbelanja secara spontan, sejumlah konsumen tidak berbelanja tanpa berpikir panjang, dan sejumlah konsumen tidak berbelanja karena pertimbangan emosi. Penelitian ini menggunakan metode survey dengan menggunakan teknik non-probability sampling untuk pengambilan sampel. Dan jenis teknik non-probability sampling yang dipilih ialah teknik insidential sampling. Penelitian ini menggunakan jenis penelitian verifikatif deskriptif dengan pendekatan kuantitatif. Populasi dalam penelitian ini merupakan konsumen produk Eiger di Kota Subang. Penelitian ini mengambil sampel sebanyak 100 orang responden. Analisis regresi linier berganda adalah metode analisis data yang digunakan dalam penelitian ini yang bertujuan untuk mengetahui arah hubungan antara variabel independen yaitu Hedonic Shopping Motivation (X1) dan E-WOM (Electronic Word of Mouth) (X2) dengan variabel dependen yaitu Impulse Buying (Y). Hasil pengujian ini menyatakan bahwa variabel Hedonic Shopping Motivation dan E-WOM (Electronic Word of Mouth) masing-masing secara parsial berpengaruh signifikan terhadap Impulse Buying, dan secara simultan variabel Hedonic Shopping Motivation dan E-WOM (Electronic Word of Mouth) berpengaruh signifikan terhadap Impulse Buying pada produk Eiger.